Effects of rural domestic sewage reclaimed irrigation and regulation on heavy metals, PPCPs, water and nitrogen utilization, and microbial diversity in paddy field - Zheng, Shizong; Xiao, Menghua; Wang, Lei; Li, Yuanyuan; Xiao, Wanchuan; Xu, Dan; Cai, Jiafang (International Journal of Agricultural and Biological Engineering, 2023)
Rural domestic reclaimed water (RDRW) is rural domestic sewage that being safely treated, the irrigation and reuse of RDRW are an effective way to alleviate the contradiction between supply and demand of water resources in South China. In this study, four kinds of irrigation water sources (primary and secondary treated water R1 and R2, purified water R3 and river water CK) and three kinds of water level regulations (low, medium, and high field water level control of W1, W2 and W3) were set to study the impact of RDRW on soil and crop safety, water and nitrogen utilization and biodiversity for establishing the regulation mechanism of RDRW irrigation with field experiment, and monitoring was carried out in RDRW irrigation demonstration area to assess the effectiveness of RDRW. The results showed that, under RDRW irrigation, the contents of Cd and Pb increased slightly, while the contents of Cr, Cu and Zn decreased in paddy soil. The heavy metals content decreased along the direction of stem, leaf and grain in rice plants, but did not increase significantly in rice grains. With the increase of field water level, pharmaceutical and personal care products (PPCPs) content in 60-80 cm soil layer was accumulated, and the PPCPs content in rice husks was higher than that in grains, but it was at a very low level. Compared to CK, RDRW irrigation can effectively increase rice yield, rainwater use efficiency (RUE) and nitrogen use efficiency (NUE) by 5.4%-7.6%, 6.7%-9.4% and 21.7%-24.2%, respectively, and the species diversity, community diversity and richness in rice fields were improved. Additionally, water level regulation of W3 with R2 water resource irrigation was conducive to the exertion of comprehensive benefits. The monitoring of demonstration area showed that the consumption of fresh water was reduced by 530 mm, yield was increased by 9.6%, and the soil and crop were both safety. Short-term irrigation of RDRW did not cause soil and crops pollution, however, it is still necessary to track and monitor the effect of the system on soil, crop, and underground water with long-term reclaimed water irrigation.Keywords: reclaimed water irrigation, heavy metals, pharmaceutical and personal care products, water and nitrogen use efficiency, soil microbial diversity, technique for order preference by similarity to an ideal solutionDOI: 10.25165/j.ijabe.20231604.7657Citation: Zheng S Z, Xiao M H, Wang L, Li Y Y, Xiao W C, Xu D, et al. Effects of rural domestic sewage reclaimed irrigation and regulation on heavy metals, PPCPs, water and nitrogen utilization, and microbial diversity in paddy field. Int J Agric & Biol Eng, 2022; 16(4): 245–256.